Developing a Model of Prolonged Grief Based on Adverse Childhood Experiences with the Mediating Role of Perceived Social Support among Survivors of the COVID-19 Pandemic - Nikkhah, Parvaneh; Niusha, Beheshteh; Haghighat-Manesh, Elaheh (Mental Health and Lifestyle Journal, 2025)
This study aimed to investigate the direct and indirect effects of adverse childhood experiences on prolonged grief among survivors of the COVID-19 pandemic, with perceived social support as a mediating variable. The study employed a correlational design using structural equation modeling. The statistical population included bereaved individuals in Alborz Province who lost at least one first-degree family member due to COVID-19. A total of 361 participants were recruited through convenience sampling via online surveys conducted between June and November 2024. Data were collected using the Prolonged Grief Disorder Scale (PG-13-R), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Childhood Trauma Questionnaire–Short Form (CTQ-SF). Descriptive statistics, Pearson correlations, multiple regression analyses, and structural equation modeling were applied to analyze the data. Model fit indices confirmed the adequacy of the tested model. Regression analyses indicated that social support from family (β = -0.31, p < 0.001), significant others (β = -0.33, p < 0.001), and friends (β = -0.02, p < 0.001) negatively predicted prolonged grief, explaining 42% of the variance. Adverse childhood experiences, including emotional abuse (β = 0.47, p < 0.001) and emotional neglect (β = 0.54, p < 0.001), significantly predicted prolonged grief, accounting for 53% of the variance. Structural equation modeling revealed that adverse childhood experiences directly increased prolonged grief (β = 0.79, p = 0.05) and indirectly heightened grief by reducing perceived social support (β = -0.96, p < 0.001). Bootstrap analysis confirmed the significance of this indirect pathway (95% CI = 0.41–0.66, p < 0.001). The findings demonstrate that prolonged grief among COVID-19 survivors is shaped both by early developmental adversities and by the availability of perceived social support. Trauma-informed interventions that simultaneously strengthen social support networks may be effective in alleviating prolonged grief.